The Efficacy of a gamified virtual reality environment combined with tDCS in treadmill-based gait rehabilitation for Parkinson’s disease - Bosch-Barceló, Pere (fi=Turun yliopisto|en=University of Turku|, 2025)
Objectives: The general objective of this dissertation was to determine the efficacy of combining a gamified virtual reality environment (GVRE) with transcranial direct current stimulation (tDCS) in treadmill-based gait rehabilitation for individuals with Parkinson’s disease (PD). To achieve this goal, we set several specific objectives: (1) to synthesize existing evidence on the use of gamification in technological devices for motor rehabilitation in PD (article I), (2) to design, develop, and evaluate the feasibility of a GVRE gait rehabilitation intervention tailored to people with PD (article II), (3) to design a study protocol for a randomized controlled trial (RCT) evaluating the combined intervention of GVRE and tDCS in gait rehabilitation for PD (article III), and (4) to assess preliminary outcomes from the RCT regarding gait variables, clinical assessment and user experience (article IV). Methodology: To address specific objectives 1 and 2, a scoping review and a co-creation feasibility study were conducted. The scoping review identified the extent and characteristics of gamified technology use in PD rehabilitation. The feasibility study was carried out using participatory design methodologies with people with PD and healthcare professionals. To address objectives 3 and 4, a mixed-methods RCT was developed and conducted. The trial enrolled individuals with PD to randomly receive gait rehabilitation training in one of three groups: (1) treadmill + GVRE + tDCS; (2) treadmill + GVRE; (3) treadmill. Quantitative outcomes included gait parameters, executive function assessment and clinical measures; qualitative data captured participant experience and satisfaction. Results: Gamification was found to enhance motivation, engagement, and adherence in PD rehabilitation technologies. The designed intervention was feasible and well-received, emphasizing simplicity, personalization, and safety. Preliminary findings from the RCT suggest that the combined use of treadmill, GVRE and tDCS is not significantly better at improving gait parameters than its control counterparts. However, participants in the Treadmill+GVRE and Treadmill+GVRE+tDCS groups reported subjective improvements in stride regulation, walking confidence, and cognitive awareness. Select cognitive gains, including improved inhibitory control, emerged at follow-up, suggesting possible delayed effects of neuromodulation. Participants reported high acceptability and engagement to the GVRE intervention. Conclusions: The integration of GVRE and tDCS into gait rehabilitation for PD proved an effective tool to enhance engagement, but potential improvements regarding gait-related outcomes are unclear. Future research should aim to conduct further research with larger, more diverse sample sizes and further personalize gamified content based on aimed experience and characteristics of individuals with PD. Interventions should aim to balance cognitive load, physical challenge, and motivational support to meet the unique needs of people with PD.

L’eficàcia d’un entorn de realitat virtual gamificat combinat amb tDCS en la rehabilitació de la marxa en cinta de córrer per a la malaltia de Parkinson Objectius: L’objectiu general d’aquesta tesi ha estat determinar l’eficàcia de combinar un entorn de realitat virtual gamificat (GVRE) amb estimulació transcranial per corrent directa (tDCS) en la rehabilitació de la marxa mitjançant cinta de córrer en persones amb malaltia de Parkinson (PD). Per assolir aquest objectiu, es van establir diversos objectius específics: (1) sintetitzar l’evidència existent sobre l’ús de la gamificació en dispositius tecnològics per a la rehabilitació motora en la PD (article I), (2) dissenyar, desenvolupar i avaluar la viabilitat d’una intervenció de rehabilitació de la marxa mitjançant GVRE adaptada a persones amb PD (article II), (3) dissenyar un protocol d’estudi per a un assaig clínic aleatoritzat (RCT) que avalués la intervenció combinada de GVRE i tDCS en la rehabilitació de la marxa per a la PD (article III), i (4) analitzar els resultats preliminars del RCT pel que fa a variables de la marxa, avaluacions clíniques i experiència d’usuari (article IV). Metodologia: Per abordar els objectius específics 1 i 2, es van dur a terme una revisió exploratòria i un estudi de viabilitat mitjançant co-creació. La revisió exploratòria va identificar l’abast i les característiques de l’ús de la tecnologia gamificada en la rehabilitació de la MP. L’estudi de viabilitat es va desenvolupar amb metodologies de disseny participatiu amb persones amb PD i fisioterapeutes. Per als objectius 3 i 4, es va dissenyar i executar un RCT amb enfocament mixt. L’assaig va incloure persones amb PD aleatoritzades en tres grups d’entrenament de la marxa: (1) cinta de córrer + GVRE + tDCS; (2) cinta de córrer + GVRE; (3) només cinta de córrer. Els resultats quantitatius incloïen paràmetres de marxa, proves de funció executiva i mesures clíniques; les dades qualitatives recollien l’experiència i satisfacció dels participants. Resultats: La gamificació va demostrar afavorir la motivació, implicació i adherència en tecnologies de rehabilitació per a la MP. La intervenció dissenyada va resultar viable i ben acollida, destacant-se per la seva simplicitat, personalització i seguretat. Els resultats preliminars del RCT suggereixen que la combinació de cinta de córrer, GVRE i tDCS no millora significativament els paràmetres de marxa respecte als grups control. Tanmateix, els participants dels grups Cinta+GVRE i Cinta+GVRE+tDCS van reportar millores subjectives en la regulació de la foulada, confiança en la marxa i consciència cognitiva. Es van observar alguns guanys cognitius, com la millora del control inhibitori en el seguiment, suggerint possibles efectes retardats de la neuromodulació. L’acceptació i implicació amb la GVRE va ser alta entre els participants, tot i que el gaudi va ser variable. Conclusions: La integració del GVRE i la tDCS en la rehabilitació de la marxa per a la PD es mostra com una eina prometedora per millorar la implicació, tot i que els efectes sobre els resultats motors objectius romanen incerts. Futurs estudis haurien de completar l’RCT amb una mostra més àmplia i diversa, i personalitzar encara més els continguts gamificats segons les característiques i experiències de les persones amb MP. Les intervencions han de buscar un equilibri entre càrrega cognitiva, desafiament físic i suport motivacional per adaptar-se a les necessitats específiques d’aquesta població.

Pelillistetyn virtuaalitodellisuusympäristön ja tDCS:n yhdistelmän teho juoksumattopohjaisessa kävelykuntoutuksessa Parkinsonin tautia sairastavilla Tavoitteet: Tämän väitöskirjatutkimuksen päätavoitteena oli arvioida pelillisen virtuaalitodellisuusympäristön (GVRE) ja transkraniaalisen tasavirta-stimulaation (tDCS) yhdistämisen vaikuttavuutta Parkinsonin tautia (PD) sairastavien henkilöiden juoksumatolla toteutettavassa kävelykuntoutuksessa. Tutkimukselle asetettiin seuraavat alatavoitteet: (1) koota ja analysoida olemassa oleva tutkimusnäyttö pelillisyydestä PD-potilaiden motorisen kuntoutuksen teknologioissa (artikkeli I), (2) suunnitella, kehittää ja arvioida GVRE-pohjaisen kävelykuntoutusintervention soveltuvuutta GVRE-pohjaisen kävelykuntoutusintervention soveltuvuutta ja hyväksyttävyyttä PD-potilaiden näkökulmasta (artikkeli II), (3) laatia satunnaistetun kontrolloidun tutkimuksen (RCT) tutkimusprotokolla yhdistetyn GVRE- ja tDCS-intervention vaikuttavuuden arvioimiseksi (artikkeli III), ja (4) arvioida RCT-tutkimuksen alustavia tuloksia kävelymuuttujien, kliinisten mittarien ja käyttäjäkokemusten osalta (artikkeli IV). Menetelmät: Tavoitteiden 1 ja 2 saavuttamiseksi toteutettiin kirjallisuuskatsaus ja yhteiskehittämiseen perustuva soveltuvuustutkimus. Soveltuvuustutkimus toteutettiin yhteiskehittämisen menetelmin yhteistyössä PD-potilaiden ja terveydenhuollon ammattilaisten kanssa. Tavoitteiden 3 ja 4 osalta suunniteltiin ja toteutettiin monimenetelmällinen RCT-tutkimus, jossa osallistujat jaettiin satunnaisesti kolmeen ryhmään: (1) juoksumatto + GVRE + tDCS, (2) juoksumatto + GVRE, (3) pelkkä juoksumatto. Kvantitatiivinen aineisto koostui kävelyparametreista, toiminnanohjauksen arvioista ja kliinisistä mittareista, kun taas kvalitatiivinen aineisto keräsi tietoa osallistujien kokemuksista ja tyytyväisyydestä interventioon. Tulokset: Pelillisyyden havaittiin edistävän motivaatiota, sitoutumista ja hoitoon sitoutumista PD-potilaiden kuntoutusteknologioissa. Soveltuvuustutkimuksen tulosten mukaan interventio oli toteuttamiskelpoinen ja osallistujien mielestä selkeä, turvallinen ja yksilöllisesti räätälöitävissä. RCT-tutkimuksen alustavat tulokset viittaavat siihen, että juoksumaton, GVRE:n ja tDCS:n yhdistelmällä ei saavuteta merkittävästi parempia kävelytuloksia verrattuna kontrolliryhmiin. GVRE- ja tDCS-ryhmissä osallistujat raportoivat kuitenkin subjektiivisia parannuksia askelpituuden hallinnassa, kävelyvarmuudessa sekä kognitiivisessa tietoisuudessa. Lisäksi joitakin kognitiivisia hyötyjä, kuten estokyvyn paranemista, ilmeni viiveellä, mikä voi viitata transkraniaalisen neuromodulaation viivästyneisiin vaikutusmekanismeihin. Osallistujat suhtautuivat interventioon pääosin myönteisesti ja sitoutuivat siihen hyvin, vaikka GVRE-ympäristön koettu miellyttävyys vaihteli yksilöiden välillä. Johtopäätökset: GVRE:n ja tDCS:n yhdistäminen Parkinsonin taudin kävelykuntoutukseen näyttäytyy lupaavana lähestymistapana erityisesti osallistujien sitoutumisen vahvistamisessa, vaikka vaikutukset objektiivisiin kävelyparametreihin jäävät edelleen epäselviksi. Jatkossa tutkimusten tulisi hyödyntää suurempia ja heterogeenisempiä otoksia sekä kehittää pelillisten sisältöjen yksilöllistämistä PD-potilaiden tarpeiden ja kokemusten mukaisesti. Interventioiden suunnittelussa olisi pyrittävä tasapainottamaan kognitiivinen kuormitus, fyysinen haastavuus ja motivaation tukeminen, jotta ne vastaisivat PD:n monimuotoisiin kuntoutustarpeisiin mahdollisimman tarkasti.